Design and Validation of Sleep Apnea Risk Assessment (SARA): A Screening Tool for Moderate-to-Severe Obstructive Sleep Apnea - Solecka S; Tomaskova H; Chudy M; Kostlivy T; Slonkova J (Nature and Science of Sleep)
Sarka Solecka,1– 3 Hana Tomaskova,3 Milos Chudy,3,4 Tomas Kostlivy,5 Jana Slonkova4,6 1Department of Otorhinolaryngology, St Luke’s Hospital, Bielsko-Biala, 43-309, Poland; 2Department of Otorhinolaryngology, Hospital in Frýdek-Místek, Frýdek-Místek, 738 01, Czech Republic; 3Department of Epidemiology and Public Health, Faculty of Medicine, University of Ostrava, Ostrava, 70103, Czech Republic; 4Department of Neurology, University Hospital Ostrava, Ostrava- Poruba, 708 52, Czech Republic; 5Department of Otorhinolaryngology, University Hospital in Pilsen, Faculty of Medicine in Pilsen, Charles University, Pilsen, 301 00, Czech Republic; 6Department of Clinical Neurosciences, Faculty of Medicine, University of Ostrava, Ostrava, 703 00, Czech RepublicCorrespondence: Jana Slonkova, Department of Neurology, University Hospital Ostrava, 17. listopadu 1790, Ostrava- Poruba, 708 52, Czech Republic, Tel +420608742273, Email jana.slonkova@fno.czPurpose: We designed and validated a concise, efficient screening tool, the Sleep Apnea Risk Assessment (SARA), to identify patients at high risk of moderate to-severe obstructive sleep apnea.Patients and methods: We conducted a two-phase, multicenter study from September 1, 2018, to October 31, 2023. We created Cohort A (n=221, mean age 50.5± 13.0 years, 69.2% male) to design SARA and compared the results with the Epworth Sleepiness Scale, Berlin Questionnaire, Pittsburgh Sleep Quality Index, STOP-Bang, and STOP questionnaires. Cohort B (n=253, mean age 48.0± 13.4 years, 75.5% male) served for validation.Results: SARA comprises six variables with the highest accuracy: sleep apnea observed by the bedroom partner (8 points), snoring (5 points), male sex (3 points), age≥ 50 years (3 points), daytime fatigue (3 points), and body mass index≥ 30 kg/m2 (2 points). SARA yielded an area under the receiver operating characteristic curve (AUC) of 0.77 (95% CI: 0.71– 0.83) and sensitivity of 87.2% (95% CI: 80.8– 92.1) in cohort A at a cut-off score of ≥ 11 points. Validation in cohort B showed an AUC of 0.79 (95% CI: 0.74– 0.84) and a sensitivity of 98% (95% CI: 89.2– 95.4). SARA performance significantly outperformed the other questionnaires tested.Conclusion: The SARA is a promising new screening tool for moderate-to-severe obstructive sleep apnea, demonstrating high sensitivity and a strong ROC curve. Further large-scale validation is recommended.Keywords: Berlin questionnaire, Epworth sleepiness scale, obstructive sleep apnea, SARA, screening questionnaire, STOP-bang